Two cationic porphyrin isomers showing different multimeric G-quadruplex recognition specificity against monomeric G-quadruplexes. Issue 13 (17th June 2014) - Huang, Xiao-Xi; Zhu, Li-Na; Wu, Bin; Huo, Yan-Fang; Duan, Na-Na; Kong, De-Ming
Abstract: Ligands that can interact specifically with telomeric multimeric G-quadruplexes could be developed as promising anticancer drugs with few side effects related to other G-quadruplex-forming regions. In this paper, a new cationic porphyrin derivative, m -TMPipEOPP, was synthesized and characterized. Its multimeric G-quadruplex recognition specificity under molecular crowding conditions was compared to its isomer p -TMPipEOPP. The slight structural difference accounts for different multimeric G-quadruplex recognition specificity for the two isomers. p -TMPipEOPP can barely discriminate between multimeric and monomeric G-quadruplexes. By contrast, m -TMPipEOPP can bind with multimeric but not with monomeric G-quadruplexes. p -TMPipEOPP might bind to multimeric G-quadruplexes by two modes: sandwich-like end-stacking mode and pocket-dependent intercalative mode. Increasing the pocket size between adjacent two G-quadruplex uints is beneficial for the latter mode. m -TMPipEOPP might bind to multimeric G-quadruplexes by a side binding mode, which confers m -TMPipEOPP with higher multimeric G-quadruplex recognition specificity compared to p -TMPipEOPP. m -TMPipEOPP increases the stability of multimeric G-quadruplex under both dilute and molecular crowding conditions but its G-quadruplex-stabilizing ability is a little weaker than p -TMPipEOPP. These results provide important information for the design of highly specific multimeric G-quadruplex ligands. Another interesting finding is that pocket size is an important factor in determining the stability of multimeric G-quadruplexes.